2002
DOI: 10.1128/mcb.22.22.7877-7888.2002
|View full text |Cite
|
Sign up to set email alerts
|

The Retinoblastoma Protein Binds the Promoter of the Survival Gene bcl-2 and Regulates Its Transcription in Epithelial Cells through Transcription Factor AP-2

Abstract: The retinoblastoma (RB) gene product has been shown to restrict cell proliferation, promote cell differentiation, and inhibit apoptosis. Loss of RB function can induce both p53-dependent apoptosis and p53-independent apoptosis; little is known about the mechanisms of RB-regulated p53-independent apoptosis. Here we show that RB specifically activates transcription of the survival gene bcl-2 in epithelial cells but not in NIH 3T3 mesenchymal cells. This transcriptional activity is mediated by the transcription f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
50
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(56 citation statements)
references
References 55 publications
4
50
0
Order By: Relevance
“…AP-2a has been shown to inhibit the activation of apoptosis mediated by the proto-oncogene c-myc, 42 and recently, AP-2a has been implicated in the antiapoptotic effects of the retinoblastoma gene product and in the induction of Bcl-2 in epithelial but not in NIH 3T3 mesenchymal cells. 43 AP-2a has also been recently reported to interact directly with p53 and to augment p53 transcriptional activation. 33 This finding would be in line with our data that Bax, a classical proapoptotic target gene of p53, is increased after overexpression of AP-2a.…”
Section: Discussionmentioning
confidence: 96%
“…AP-2a has been shown to inhibit the activation of apoptosis mediated by the proto-oncogene c-myc, 42 and recently, AP-2a has been implicated in the antiapoptotic effects of the retinoblastoma gene product and in the induction of Bcl-2 in epithelial but not in NIH 3T3 mesenchymal cells. 43 AP-2a has also been recently reported to interact directly with p53 and to augment p53 transcriptional activation. 33 This finding would be in line with our data that Bax, a classical proapoptotic target gene of p53, is increased after overexpression of AP-2a.…”
Section: Discussionmentioning
confidence: 96%
“…Importantly, we demonstrated that androgen-induced suppression of Bcl-2 expression was abolished by specific inactivation of RB function by the mutated E1A. Recently, Decary et al (2002) demonstrated that overexpression of RB protein transactivates expression of the Bcl-2 gene in kidney and breast epithelial cells and that this activation is mediated the P2 promoter. The transactivation of Bcl-2 by RB relies completely on expression of the AP2 transcription factor, since no effect of RB on Bcl-2 expression has been found in cells without AP2 expression (Decary et al, 2002).…”
Section: Expression Of the Erk2 Protein Was Used For Protein Loading mentioning
confidence: 95%
“…Recently, Decary et al (2002) demonstrated that overexpression of RB protein transactivates expression of the Bcl-2 gene in kidney and breast epithelial cells and that this activation is mediated the P2 promoter. The transactivation of Bcl-2 by RB relies completely on expression of the AP2 transcription factor, since no effect of RB on Bcl-2 expression has been found in cells without AP2 expression (Decary et al, 2002). Indeed, no AP2 mRNA has been detected by Northern blot analyses in either LNCaP or PC-3 prostate cancer cells (Butler et al, 2000).…”
Section: Expression Of the Erk2 Protein Was Used For Protein Loading mentioning
confidence: 99%
“…In support of this hypothesis, TFAP2A has already been shown to physically interact with pRB in vitro and associates with pRB in vivo (Wu and Lee, 1998). Furthermore, pRB regulates the transcription of E-cadherin and BCL2 in epithelial cells through interaction with TFAP2 (Batsche et al, 1998;Decary et al, 2002).…”
Section: Discussionmentioning
confidence: 60%
“…For example, TFAP2A and TFAP2B interact with pRB in vitro (Wu and Lee, 1998), and transcription of genes such as BCL2 and E-cadherin is mediated by pRB interacting with TFAP2 (Batsche et al, 1998;Decary et al, 2002). To address a possible role for TFAP2 in retinoblastoma, we have studied the expression of TFAP2A and TFAP2B in human retina and in retinoblastoma tumors and cell lines.…”
Section: Introductionmentioning
confidence: 99%